Les aspects de la traduction qui sous-tendent l’aacquisition de la compétence de communication chei les apprenants du français langue étrangère - Szeflińska, Magdalena (Wydawnictwo Naukowe UAM, 2001)
The article discusses the role of translation in communicative teaching methods. Expunged from language teaching, translation is now coming back thanks to the introduction of communicative teaching methods. Teachers, however, are not prepared for this and the real questions still have to be asked: “Why translate in class?” The various translation exercises increase the effectiveness of teaching and learning and students’ motivation. La
On the influence of translation in acquisition of a foreign language in communicative teaching methods